Development of Interactive Mobile Learning (IMOLE) Learning Media Assisted by iSpring Suite to Improve IPAS Learning Outcomes in Elementary Schools - Khasanah, Nikmatul; Setyasto, Novi (Postgraduate, University of Mataram, 2024)
The lack of student activity in the learning process at SDN 1 Loram Kulon has an impact on student learning outcomes. This research is Research and Development which refers to the ADDIE model. This research aims to develop and test the feasibility, practicality, and effectiveness of Interactive Mobile Learning (Imole) assisted by iSpring Suite. The population in this study was 32 people with 12 small-scale test subjects in class VI students and 21 large-scale test subjects in class V at SDN 1 Loram Kulon. Data collection techniques use test (pretest-posttest) and non-test techniques in the form of observations, questionnaires, interview results, and documentation data. Validation results by material expert validators and media experts show that Interactive Mobile Learning (Imole) assisted by iSpring Suite has met the valid criteria with an average score of 93%. Based on the pretest-posttest results, it is known that Interactive Mobile Learning (Imole) assisted by iSpring Suite is effective in improving student learning outcomes with the result of an increase in the average pretest score of 50.95 to 84 at the time of the posttest and the N-gain test results obtained <g> The gain value is 0.70 in the high category. Based on the results of the response questionnaire distributed, very positive responses were obtained from teachers and students. Based on these results, it can be concluded that Interactive Mobile Learning (Imole) assisted by iSpring Suite is effective in improving science and science learning outcomes and is feasible and practical to use in the learning of class V students at SDN 1 Loram Kulon.